2016
DOI: 10.2139/ssrn.2778090
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education, Divorce, and Changes in Economic Resources: Evidence from Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…This may further exacerbate preexisting inequalities in mental health for low-SES groups. Leopold and Leopold [23], however, demonstrated that divorce is not as consequential for women with lower education as for those with higher levels of educational attainment in younger age groups, because the latter group may have more to lose.…”
Section: Introductionmentioning
confidence: 99%
“…This may further exacerbate preexisting inequalities in mental health for low-SES groups. Leopold and Leopold [23], however, demonstrated that divorce is not as consequential for women with lower education as for those with higher levels of educational attainment in younger age groups, because the latter group may have more to lose.…”
Section: Introductionmentioning
confidence: 99%
“…This expectation was not confirmed in our models. It could be the case that experiencing such fundamental changes in social roles and the reconfiguration of relationships between family members after a divorce or separation (Amato 2010;Bengtson and Allen 2009) may have the effect of 'leveling' or reducing social differentiation between parents (Leopold and Leopold 2016). Or, in other words, union dissolution itself may leave a more permanent mark on or represent a "turning point" for all families, regardless of prior SES or subsequently chosen custody arrangement, which would explain the lack of differences between the custody arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, previous empirical evidence shows that the differential effect of family type on child well-being according to the educational attainment of parents seems to be influenced by multiple factors such as, for example, the indicator of well-being under analysis or the country being studied (Bernardi & Boertien, 2017;Garriga & Berta, 2018;Grätz, 2015;Mandemakers & Kalmijn, 2014). In this sense, in countries where there is greater protection against poverty and precarity, single parenthood may not have a big impact on the economic situation of families with less educational attainment (Garriga & Berta, 2018;Leopold & Leopold, 2016). In consequence, in order to better understand the effect of educational gradient on child inequality, more empirical evidence and indicators that analyse different contexts must be taken into account.…”
Section: Interpretative and Hypothetical Modelmentioning
confidence: 95%